PERSEPSI PESERTA TERHADAP PELAKSANAAN PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE DI DESA KARYA MUKTI KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Catur Nanang Prasetyo; Aswandi Bahar; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on the state of facilities and in the implementation of the martial arts it can be said support, although not sufficient. Formulation problems research is whether perception participants with the implementation of the Pencak Silat Persaudaraan Setia Hati Terate di Desa Karya Mukti Kecamatan Rimba Melintang Kabupaten Rokan Hilir in good?. The purpose of this research is to find perception participants with the implementation of the Pencak Silat Persaudaraan Setia Hati Terate di Desa Karya Mukti Kecamatan Rimba Melintang Kabupaten Rokan Hilir have good. Population in this study about 30 people learn. So research sample areas 30 people and the other 20 a test sample of try, sample used is sampling saturated. An instrument data collection that is chief with 57 a statement and if the trial live 55 a statement valid for in made instrument research. Data analysis through descriptive analysis quantitative. The analysis carried out in then a conclusion can be drawn on the this research note that, perception participants on the implementation of martial arts fraternity loyal terate in the heart of mukti in the wild transverse rokan downstream districts have good, seen from the input, the process, and output. Then input indicators most best and has the percentage of the average value of 82 % . It means participants assume of teaching staff or his coach very disciplined and having good performance.Key words: Perception, perception participants